Implementation of panipati method on memorization the Quran in Malaysia: A study in tahfiz institute - Sadek, A.; Mustaffa, A.; Mohd Yusoff, Mohd Yakub @ Zulkifli; Ahmad, Khadher (2014)

(untitled)
Until today, memorization is still one of the methods used in the process of preservation of the Qur'an. This article aims to review and analyze the methods and approaches used by a Centre of Tahfiz Quran Lorong Alif Jitra Kedah in the process to produce the students that can remember the whole Qur'an. This study used the methods of documentation, observation and interviews in order to obtain the data. Through the analysis, this study found that there are seven basic methods of memorizing the Quran; Sabak, Nam Sabak, Sabki, Separah, Mutlaah, Tertib Wifak and Dastar Bandi. By using these seven methods, the students could recite the whole Qur'an by memorization, without seeing the mushaf. As a researcher, I would like to suggest these 'methods of memorization, to be applied in all the centers, in order to produce the huffaz who can fully memorizing the Quran.